PEMBUATAN MEDIA PROMOSI E-CATALOG DI INSTAGRAM MENGGUNAKAN APLIKASI CORELDRAW PADA ANNAFA FOOD BLITAR - Khairun Nisa, Imelda; Tri Ramadani Arjo; Rr. Tri Istining Wardani (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
This study focuses on Annafa Food Blitar, a culinary business offering cakes, snacks, and rice boxes, which promotes its products through Instagram and WhatsApp Business. However, the Instagram promotions were deemed less effective due to insufficient product details. The research aimed to develop an effective E-catalog using CorelDraw as a promotional tool. An action research method was employed, involving planning, action, observation, and reflection. Data was collected through observations, interviews, documentation, and questionnaires distributed to 17 respondents, including the business owner, employees, design and marketing experts, and potential customers. The EPIC Model was used to evaluate the E-catalog's effectiveness. The findings suggest that the E-catalog designed with CorelDraw is a highly effective promotional tool. Continuous updates are recommended to keep it appealing to potential customers. Keywords: Promotional Media, E-catalog, CorelDraw, Annafa Food Blitar